Kesepakatan Menunda Kehamilan Bagi Pasangan Muda Perspektif Hukum Islam: Upaya Menekan Pernikahan Dini di Masa Pandemi - Anton Jamal; M. Ikhwan (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2021)
This research is an attempt to look deeper into why delaying early marriage is appropriate during the COVID-19 pandemic based on the view of Islamic law and the human rights approach. The phenomenon of early marriage during the pandemic had appeared and even jumped based on the data collected. This phenomenon encourages conditions of vulnerability (fiqh: mudharat) which will have an impact on the emergence of new problems and even conflicts for young people, especially if they already have children, given the pandemic conditions that often threaten the household economy. This study departs from the question of why Islamic law and human rights must play a role in reducing the number of early marriages during the pandemic based on the assumption of household vulnerability? How is the phenomenon of early marriage during the pandemic seen from the point of view of human rights and maqasid? This research is analytical descriptive with qualitative methods, and data collection is carried out by literature study on secondary materials to observe the phenomenon of early post-marriage during the pandemic. The results show that the function of Islamic law and human rights can be an important instrument to suppress the surge in early marriage, which will save young households from the vulnerability of household conflicts based on observations made during the covid pandemic.